KAJIAN TENTANG POLITIK HUKUM UNDANG-UNDANG NOMOR 13 TAHUN 2012 TENTANG KEISTIMEWAAN DAERAH ISTIMEWA YOGYAKARTA - Suparno*), Dian Putri Pratama, Retno Saraswati, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
The Indonesian constitutional system has changed much. The case was marked by the presence of four amendments to the 1945 Constitution. The results of the second amendment of the 1945 Constitution, specifically adds a special article about the privileged area. The focus of the research problem lies in how the region is positioned privileged in the state system in Indonesia. Furthermore, the focus of the next issue is about the assessment of the legal policy in Privilege Act Yogyakarta. Legal policy is the policy line of the law to be applied to both with the new law and the replacement of the old law order to achieve the objectives as stated in the 1945 Constitution. The Research with title